FENOMENA SELFIE (SELF PORTRAIT) DI INSTAGRAM (Studi Fenomenologi Pada Remaja Di Kelurahan Simpang Baru Pekanbaru) - Simatupang, Fritta Faulina; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Selfie (self portrait) became a phenomenon that 'infect' almost everyone, from children, adolescent and adults. Many people do selfie (self portrait) and then upload to instagram with some reasons and aims, such as hobbies, attentions or existence from others who see their selfie (self portrait) in instagram. This research was done for seeing the reality of self concept of adolescents who live in Simpang Baru village when doing selfie (self portrait) and uploaded to instagram. This research used qualitative methode by phenomenological approach. In order to obtain the data, the researcher used three kinds of data collection techniques, such as participant observation, in-depth interview, and documentation. This research used data’s analysis technique of phenomenological research according to Creswell by using the technique of persistence observation, extension of participation, and the adequacy of reference. The result showed the first, that adolescents who did selfie (self portrait) and then upload to instagram have two kinds of self concept, which are positive self concept and negative self concept. That self concept is seen from how the adolescents see and assess themselves and their performanace before doing selfie (self portrait) as well as the way adolescents and significant others interpret selfie (self portrait) that was done. Second, the photo of selfie (self portrait) which were uploaded to instagram influenced by adolescents of past motives so that encourage them to achieve something from selfie (self portrait). The photo of selfie (self portrait) which they uploaded to instagram make them get the sepecific identity based on the criteria.Keywords: Selfie (Self Portrait), Instagram, Adolescent, Phenomenological, Simbolic Interaction Theory.